Levels of regulatory B cells do not predict serological responses to hepatitis B vaccine - Maria Bolther; Karen Lise Dahl Andersen; Martin Tolstrup; Kumar Visvanathan; Ian Woolley; Narelle Skinner; Rosemary Millen; Nadia Warner; Lars Østergaard; Søren Jensen-Fangel (Taylor & Francis Group, 2018)
This study investigated the immunomodulatory influence of IL10 producing B regulatory cells, Bregs (CD19+CD24hiCD38hi) to standard Twinrix® vaccination. We also investigated HBsAg specific T-cell mediated IFN-γ responses to Twinrix® which in theory could provide effective immunity despite low anti-HBs titer. A total of 309 hepatitis B negative health care students and workers completed a standard Twinrix® vaccination schedule (0, 1 and 6 months). Depending on the vaccination response the participants were divided in to non-, low- and high responders according to anti-HBs titer (<10, <100 and >1000 mIU/mL respectively) two months after completed vaccination schedule. Blood samples from baseline and after vaccination from all non- and low-responders (23 participants) and the same number of high-responders were used for flow cytometric analyses of IL10 producing Bregs and T-cell mediated IFN-γ responses. A decrease in levels of IL10 producing Bregs was observed after vaccination in high responders compared to non- and low-responders. Compiling non-and low-responders against high-responders showed a lower T-cell mediated IFN-γ response at baseline in non-and low-responders when stimulated with Engerix® vaccine. In contrary no positive correlation between IL10 producing Bregs or IFN-γ positive T-cells and anti-HBs titer was observed. Hence this study cannot prove that levels of IL10 producing Bregs or IFN-γ positive T cell affect HBV vaccine response.